2018
DOI: 10.1111/jmwh.12681
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Clinical Evaluation of Acupuncture Therapy in Patients With Postpartum Sciatica

Abstract: Compared with bed rest, acupuncture might be an effective and acceptable strategy to relieve symptoms of postpartum sciatica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Our results are in line with those of recent clinical trials and meta-analyses. 16,19,20,31 In our previous review of common acupoints for treating sciatica, 24 the acupoints selected were primarily in the bladder (BL) and gallbladder (GB) meridians, as well as the Governing Vessels and Kidney (KI) meridians, which, based on TCM theory, may nourish the patient's qi. Our acupoint selection for treating sciatica was based on TCM theory and took into account a concept in contemporary medicine: the dermatome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results are in line with those of recent clinical trials and meta-analyses. 16,19,20,31 In our previous review of common acupoints for treating sciatica, 24 the acupoints selected were primarily in the bladder (BL) and gallbladder (GB) meridians, as well as the Governing Vessels and Kidney (KI) meridians, which, based on TCM theory, may nourish the patient's qi. Our acupoint selection for treating sciatica was based on TCM theory and took into account a concept in contemporary medicine: the dermatome.…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores indicated a better QOL. The WHOQOL-BREF had four subscales: (1) physical domain (score range, 4-20); (2) psychological domain (score range, 4-20); (3) social domain (score range, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; and (4) environmental domain (score range, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The total score ranged from 8 to 80 points, with higher values indicating better outcomes.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of research findings have shown that a significant decrease in the number of the cellular constituents in the degenerative intervertebral disc is one of the important reasons for extracellular substrate metabolism imbalance and decreased content [ 15 , 16 ] while apoptosis is the leading cause of the decreased number of the cells in the intervertebral disc [ 17 ]. Wu D et al have detected the apoptotic rate of the cells in the intervertebral disc of the patients with protrusion of intervertebral disc and discovered that the apoptotic rate is significantly higher than that in the healthy people [ 18 ].…”
Section: Discussionmentioning
confidence: 99%